2021
DOI: 10.3390/foods10071528
|View full text |Cite
|
Sign up to set email alerts
|

Alginate-Assisted Lemongrass (Cymbopogon nardus) Essential Oil Dispersions for Antifungal Activity

Abstract: The use of natural compounds as food preservatives is becoming increasingly popular as it is perceived positively by consumers. Among these substances, essential oils have attracted great interest owing to their antioxidant and antimicrobial properties. However, several challenges impair the use of essential oils in food products, such as their degradation or loss during food processing and storage, the strong aroma, even at low concentrations, which may negatively affect the sensory characteristics of food. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 49 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…This study showed that the assayed root and leaves of C. winterianus EOs have variable microbial inhibitory activities, as presented in Table 6 . Plants having secondary metabolites and the EOs of C. winterianus have demonstrated a broad range of antimicrobial activities against different pathogens [ 11 , 12 , 49 , 50 ]. The leaf part of C. winterianus EO showed effectiveness against Pseudomonas aeruginosa , with an MIC of 78.1 μg/mL and noticeable activity against Staphylococcus aureus , Staphylococcus epidermidis , and Streptococcus pyogenes , with an MIC of 156.3 μg/mL, while other panels of bacterial strains had no surprising results.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that the assayed root and leaves of C. winterianus EOs have variable microbial inhibitory activities, as presented in Table 6 . Plants having secondary metabolites and the EOs of C. winterianus have demonstrated a broad range of antimicrobial activities against different pathogens [ 11 , 12 , 49 , 50 ]. The leaf part of C. winterianus EO showed effectiveness against Pseudomonas aeruginosa , with an MIC of 78.1 μg/mL and noticeable activity against Staphylococcus aureus , Staphylococcus epidermidis , and Streptococcus pyogenes , with an MIC of 156.3 μg/mL, while other panels of bacterial strains had no surprising results.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, LGO‐containing samples demonstrated significant potential with antifungal action in active Alg coating, by inhibiting the spore germination of undesirable fungi. Similar results have been documented when LGO was entrapped in Alg matrix (Riquelme et al ., 2017; Gago et al ., 2019; Cofelice et al ., 2021; Kawhena et al ., 2021) and other matrices including chitosan (Shao et al ., 2015; Kawhena et al ., 2021) and starch (Perdana et al ., 2021). The active components, α‐citral (geranial) and β‐citral (neral), are believed to be potent antifungal agents contained in LGO (Lal et al ., 2016; Lal et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported the antifungal ability of Alg/LGO emulsion composite against Penicillium spp (Cofelice et al ., 2021; Kawhena et al ., 2021), Botrytis cinerea (Riquelme et al ., 2017; Gago et al ., 2019; Kawhena et al ., 2021), Rhizopus spp. (Cofelice et al ., 2021) and Aspergillus niger (Cofelice et al ., 2021). Furthermore, Alg/LGO permitted as a generally recognised as safe (GRAS) compound with acceptable daily intake (ADI) value for geraniol of 0.5 mg kg −1 body weight day −1 (Commission Implementing Regulation (EU) No 570/, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many researches have increasingly demonstrated the antimicrobial effect of different essential oils (such as cilantro, coriander, oregano, cinnamon, rosemary, sage, clove, thyme, etc.) against pathogenic bacteria and food spoilage agents [14][15][16][17] and have proposed new solutions to deliver these compounds [18,19]. Wang et al (2020) showed that ginger essential oil, where zingiberene and α-curcumene were identified as the main chemical constituents, has excellent antibacterial activity against E. coli and S. aureus [20].…”
Section: Introductionmentioning
confidence: 99%